PENGARUH TEKNIK PERNAPASAN BUTEYKO TERHADAP FUNGSI PARU PADA PASIEN ASMA BRONCHIAL - Marlin Sutrisna; Mariza Arfianti (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Bronchial asthma is an incurable disease but can be controlled or prevented from recurring. Long asthmatreatment can have side effects such as growth suppression, increased liver enzymes, headaches, nausea andosteoporosis. Therefore it is necessary to use Buteyko breathing technique as an adjuvant therapy. Buteykobreathing technique has the advantage of being easy to do, safe and has no side effects, and requires no cost.On the other hand, buteyko breathing exercises can improve lung function. This study aims to determine theeffect of Buteyko breathing technique on lung function.This quasi-experimental study uses a one group designpretest and post test approach, meaning that it is only conducted in one intervention group and there is nocontrol group. The sample in this study amounted to 14 asthma patients selected from the PulmonaryPolyclinic Of Dr. Hasan Sadikin Bandung Hospital with consecutive sampling. Buteyko breathing techniqueexercises are done 15-60 in one day, with a minimum frequency of exercise twice a week for 4 weeks.Examination of pulmonary function was carried out using spirometry (FEV1 value) at the first week pretestand the fourth week post test. The collected data were analyzed descriptively and inferentially with asignificance scale of p <0.05.Paired t-test showed a significantly higher difference (p = 0.00) in the FEV1value after administration of the buteyko breathing technique (69.57% ± 6.836) than the FEV1 value beforethe administration of the buteyko breathing technique (37.43% ± 6,513).It was concluded that there is apositive effect of the Beyko breathing technique on lung function. Thus, it is important to make the results ofthis study as a study material for health workers in hospitals in an effort to improve lung function